Child Custody in Divorce: Child Psychology Perspective - Ryan Fahri Rangkuti; Aufiya Muhammad Syukri Alghiffary; Gilang Ade Prabowo; Darmawan Setia; Zahara Ananda (ISNU Nine-Star Multidisciplinary Journal, 2025)
Divorce often leaves a profound impact, especially for children who must face significant life changes. This study aims to analyze child custody in the context of divorce, based on a child psychology perspective and applicable laws in Indonesia. The study also identifies issues related to law enforcement and its impact on children's psychological well-being. Using a qualitative approach based on literature, this study found that custody decisions that fail to address children's emotional needs can exacerbate the negative impacts of divorce. The conclusions emphasize the importance of a legal approach that considers children's psychology to ensure their well-being.